Macroeconomic Dynamics of Riau 2024: Growth, Inflation, And Financial Stability Analysis - Seswandi, Agus; Burhan, Burhan (LPPM Universitas PGRI Sumatera Barat, 2023)
The economy of Riau Province experienced a slowdown in the third quarter of 2024 due to the decline in foreign exports and government consumption, which was influenced by the economic downturn of major trading partner countries. The study aims to analyze the factors that influence economic growth, inflation, and financial stability in Riau. The method used in this research is quantitative descriptive analysis with a secondary data approach from regional economic and financial reports. The data was analyzed using a comparison of economic growth between periods and an evaluation of macroeconomic indicator trends. The research found that the economic slowdown was triggered by the decline in export demand for CPO and other plantation products, as well as the low realization of government spending. Inflation decreased in line with the national trend, mainly due to the stabilization of food and transportation prices. Meanwhile, the banking sector remained stable with an increase in lending and growth in third-party funds (DPK). The study concluded that export diversification strategies and optimization of regional spending need to be strengthened to maintain sustainable economic growth. Theoretical implications confirm the influence of fiscal policy on economic growth, while practically, policy recommendations are provided to maintain inflation and regional financial stability. The uniqueness of this research lies in the integrated analysis between external and domestic factors in influencing Riau's economy.